Principle of Leadership - DUBRIN, Andrew J. (SOUTH- WESTERN, 2009)
Perfect for instructors who take a practical, skill-building approach to teaching leadership, the Sixth Edition of PRINCIPLES OF LEADERSHIP, INTERNATIONAL EDITION provides an ideal balance of essential theory and real-world applications. Andrew DuBrin, a highly respected author and consultant, incorporates the latest research on leadership and current business practices from academic journals and popular periodicals. The text provides students with a strong practical foundation by introducing leaders they can relate to and reinforcing their knowledge with frequent skill-building activities. Key updates include new opening vignettes and end-of-chapter cases, numerous additional skill-building exercises, and an enhanced student companion site with new Knowledge Bank activities and self-assessments.